Effects of daily ingestion of fresh milk produced by cows raised in two systems on blood variables, intestinal health and weight gain in an animal model Efeitos da ingestão diária de leite in natura produzido por vacas criadas em diferentes sistemas de menejo sobre variáveis sanguíneas, saúde intestinal e ganho de peso em um modelo animal - Glombowsky P.* (2019)
© 2019, UCOPress. Cordoba University Press (UCOPress Editorial Universidad de Córdoba). All rights reserved.The objective of the present study was to evaluate whether cow’s milk produced in different systems (confinement or pasture) when consumed interferes in blood parameters and intestinal health, as well as the importance of daily milk consumption in the individual growth, an animal model. For this purpose, in natura milk from two farms with different breeding systems (Free Stall-pasture) was compared to pasteurized milk (UHT), used as control. The centesimal composition of the milks was analyzed, separated into aliquots and then frozen. 28 rats were used as experimental models (animal model) for a period of 30 days, divided into four groups with seven animals each: milk from cows raised in the Free Stall system (GFS), milk from cows raised in the pasture (GP) system, pasteurized cow’s milk (GUHT), and non-dairy animals (CG). Volume of 0.7 mL of milk was offered daily. When compared to the control group (GC) we observed a difference (P <0.05) for the following variables in serum and groups: higher protein levels-GUHT and GP; higher albumin levels-GP and GFS; higher globulin levels-GUHT; higher urea levels-GUHT, GP and GFS; lower glucose levels-GP; higher triglyceride levels in the groups that received milk-GP, GFS and GUHT; and higher cholesterol levels-GP. The villus size did not differ between the groups (P> 0.05), however, the crypt size was higher in the GP and GFS groups (P <0.05). The animals that received milk had greater weight gain (P <0.05) compared to CG. Thus, we conclude that the supply of milk with different compositions affects distinct blood variables, which stimulated crypt enhancement and weight gain.